Spinster 2, a sphingosine‐1‐phosphate transporter, plays a critical role in inflammatory and autoimmune diseases. Issue 12 (31st August 2015) - Donoviel, Michael S.; Hait, Nitai C.; Ramachandran, Subramaniam; Maceyka, Michael; Takabe, Kazuaki; Milstien, Sheldon; Oravecz, Tamas; Spiegel, Sarah
ABSTRACT: Sphingosine 1‐phosphate (S1P) is a pleiotropic bioactive sphingolipid metabolite that regulates numerous processes important for immune responses. S1P is made within cells and must be transported out of cells to exert its effects through activation of 5 specific cell surface GPCRs in an autocrine or paracrine fashion. Spinster 2 (Spns2) transports S1P out of cells, and its deletion in mice reduces circulating levels of S1P, alters immune cell trafficking, and induces lymphopenia. Here we examined the effects of Spns2 deletion on adaptive immune responses and in autoimmune disease models. Airway inflammation and hypersensitivity as well as delayed‐type contact hyper‐sensitivity were attenuated in Spns2 –/– mice. Similarly, Spns2 deletion reduced dextran sodium sulfate‐ and oxazolone‐induced colitis. Intriguingly, Spns2 –/– mice were protected from the development of experimental autoimmune encephalopathy, a model of the autoimmune disease multiple sclerosis. Deletion of Spns2 also strongly alleviated disease development in collagen‐induced arthritis. These results point to a broad role for Spns2‐mediated S1P transport in the initiation and development of adaptive immune related disorders.—Donoviel, M. S., Hait, N. C., Ramachandran, S., Maceyka, M., Takabe, K., Milstien, S., Oravecz, T., Spiegel, S. Spinster 2, a sphingosine‐1‐phosphate transporter, plays a critical role in inflammatory and autoimmune diseases. FASEB J. 29, 5018–5028 (2015). www.fasebj.org